2023
DOI: 10.1212/ne9.0000000000200048
|View full text |Cite|
|
Sign up to set email alerts
|

Scoping Review: Innovations in Clinical Neurology Education

Abstract: Advances in adult learning theory and instructional technologies provide opportunities to improve neurology knowledge acquisition. This scoping review aimed to survey the emerging landscape of educational innovation in clinical neurology. With the assistance of a research librarian, we conducted a literature search on November 4, 2021, using the following databases: PubMed, Embase, Scopus, Cochrane Library, Education Resources Information Center, and PsycINFO. We included studies of innovative teaching methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…While different journals have varying criteria for reporting an innovation, common features of a high-quality educational innovation have been defined. A recent scoping review defined 12 aspects of an educational innovation: (1) identifies a problem, (2) presents preliminary work, (3) explains what is novel, (4) presents a conceptual framework, (5) describes the implementation, (6) discusses how it was developed, (7) evaluates the innovation, (8) includes outcome data, (9) reflects on lessons learned, and (10-12) discusses sustainability, transferability, and influence on the field. 2 How are we doing in reporting high-quality innovations in neurology education?…”
Section: Innovations In Neurologic Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…While different journals have varying criteria for reporting an innovation, common features of a high-quality educational innovation have been defined. A recent scoping review defined 12 aspects of an educational innovation: (1) identifies a problem, (2) presents preliminary work, (3) explains what is novel, (4) presents a conceptual framework, (5) describes the implementation, (6) discusses how it was developed, (7) evaluates the innovation, (8) includes outcome data, (9) reflects on lessons learned, and (10-12) discusses sustainability, transferability, and influence on the field. 2 How are we doing in reporting high-quality innovations in neurology education?…”
Section: Innovations In Neurologic Educationmentioning
confidence: 99%
“…2 How are we doing in reporting high-quality innovations in neurology education? In this issue, a scoping review by Zimmerman et al 3 addresses this topic by asking 2 specific scholarly questions: (1) what educational innovations are neurology educators using and (2) how truly innovative are these interventions? The authors reviewed 350 studies and found that the most common educational innovations in neurology were simulation, eLearning, 3-dimensional modeling, virtual reality, and social media studies.…”
Section: Innovations In Neurologic Educationmentioning
confidence: 99%